PENGARUH PERHATIAN ORANG TUA DAN PERANAN AGAMA, SOSIAL DAN EKONOMI TERHADAP MOTIVASI BELAJAR SISWA DI SMA BINA SPORA MANDIRI CIGOMBONG BOGOR - Ustadz, As'ad; ifat, fatimah (Universitas Indraprasta PGRI, 2019)
The purpose of this study was to determine the influence of parents' attention on the students motivation in terms of religious, social, and economic. The research subjects were students of class X, XI, and XII SMA Bina Spora Mandiri, Cigombong, Bogor. The sample amounted to 58 students taken by total sampling technique. From the results of the calculation and analysis of research data concluded about the influences of X1 (parents role) and X2 (religious, social, economic role) to Y (student motivation). This is calculated based on the acquisition of Anova table calculated F value of 33.237 with a significant level of 0.00. With probability (sig) 0.00 or less than 0.05 (0.00 <0.05). The different between th evariables X1, X2 together with a variable Y is 0.740 with the coefficient of determination 0.547; with regard to X1, X2 together with the variable Y X1, X2 together with the variables contributing to the variable Y of 54.7%, while being the rest influenced by other factors.